(3GdJgGH fjQGf GdCMRGf heKjQ GcJFGH GdCTLGfs - (3eLghds ((3QShejgj Hf eTfhas)
(3ChdgG (B:s
(3GdMeO ddg (B... (3abO bQCJ aj GdcJH GdeGVjI hGdCNHGQ hJaUMI GdSjQ hGdBKGQ aeG hbaJ Ydi NHQ JGe jJVef haGI SjOfG QShd Gddg Udi Gddg Ydjg hSde Ydi GdJeGe hGdceGd aaJTJ GdUMa hGdBKGQ ahLOJ Pdc aj cJH eJTYHI (B...s
(3BNQgG (B:s
.. (3hUGM HZdeGfg jG hjdce SeJfj GHfJj Ce MHjH aGfgeJ Yfg abGd GdMbhgG hGbJdhNG aGZej Ydjg aCSQYhG ZdeGfg aj WdHgG djCJhG HgG hgj JYOh (B... (3JeJ gPg GdhaGI GdTQjaIs
(3JHUQI GdYfhGf (B:s
(3hjbGd dg GdJgGH GdCMRGf aj haGI SjO Hfj YOfGf GdeHYhK Ydi GdEfS hGdLGf QShd Gdedc GdefGf, heG ChUi Hg aj Mb Cgd HjJg CefGA GdQMef, heG LQi HYO haGJg ef GdGNJdGa hGdNPdGfs
(3JHUQI GdeDda (B:s
(3WHY efShHG d`(B: (3MSjf Hf eMeO Hf CMeO Hf YUahQ GdOQGRj GdHMQjfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B2\287s
Keywords: (3GdJGQjNs